A Comparison of the Pathological Types of Undifferentiated Carcinoma of the Pancreas. Issue 2 (February 2020) - Shiihara, Masahiro; Higuchi, Ryota; Izumo, Wataru; Furukawa, Toru; Yamamoto, Masakazu
Abstract : Objectives: This study aimed to identify the detailed clinicopathological features of undifferentiated carcinoma of the pancreas (UCP). Methods: We investigated clinical, imaging features and the prognoses of 261 patients; 8 were our patients, and the remainder were identified by searching English-language articles in PubMed. Results: We classified patients with UCP into 3 types based on pathological findings: osteoclast-like giant cell–associated carcinoma, pleomorphic cell carcinoma (PLC), and spindle cell carcinoma. There were no remarkable differences in clinical, radiological features between these 3 types. However, PLCs were significantly more likely to be unresectable than were the other 2 types ( P < 0.001). Patients with osteoclast-like giant cell–associated carcinoma achieved the best overall survival (OS) rates ( P < 0.001), whereas those with spindle cell carcinoma had significantly longer OS rates than did those with PLC ( P = 0.004). These OS patterns were maintained when considering only those patients who underwent resection. Patients with PLC had both lower curative resection and high lymph node metastasis rates ( P = 0.029, P = 0.023). Patients who underwent resection had more favorable prognoses than did those who did not. Conclusions: Surgery is the first choice for resectable UCP. Pleomorphic cell carcinoma is particularly malignant; postoperative treatment should be introduced immediately. Abstract : Supplemental digital content is available in the text.